Planning the Surgical Correction of Spinal Deformities: Toward the Identification of the Biomechanical Principles by Means of Numerical Simulation - Galbusera, Fabio; Bassani, Tito; La Barbera, Luigi; Ottardi, Claudia; Schlager, Benedikt; Brayda-Bruno, Marco; Villa, Tomaso; Wilke, Hans-Joachim (Frontiers in Bioengineering and Biotechnology, 2015)
The set of surgical devices and techniques to perform spine deformity correction has widened dramatically. Nevertheless, the rate of complications due to mechanical failure remains rather high. Indeed, basic research about the principles of deformity correction and the optimal surgical strategies (i.e. the choice of the fusion length, the most appropriate instrumentation, the degree of tolerable correction) did not progress as much as the techniques. In this work, a software approach for the biomechanical simulation of the correction of patient-specific spinal deformities aimed to the identification of its biomechanical principles is presented. The method is based on three dimensional reconstructions of the spinal anatomy obtained from biplanar radiographic images. A user-friendly graphical interface allows for the planning of the deformity correction and to simulate the instrumentation. Robust meshing of the instrumented spine is provided by using consolidated computational geometry and meshing libraries. Based on finite element simulation, the program predicts the loads acting in the instrumentation as well as in the biological tissues. A simple test case (reduction of a low grade spondylolisthesis at L3-L4) was simulated as a proof-of-concept. Despite the limitations of this approach, the preliminary outcome is promising and encourages a wide effort towards its refinement.